SYNTACTICAL PATTERNS OF THE INTERROGATIVE SENTENCE IN LIO LANGUAGE - Manek, Agnes Odiyanti; Sene, Chamelya V.C.; Lodo, Rozita Y.; Mola, Mansuetus; Tefa, Antonia (Metahumaniora, 2024)
This study focuses on syntactic patterns in Lio interrogative sentences, Lio is a regional language belonging to the Austronesian language family and has around 200,000 to 250,000 speakers spread across areas such as Detusoko, Wolowaru, Maurole, and Ndona. This language plays an important role in the daily lives of the Lio people, both in informal and traditional communication contexts. The main objective of this study is to describe and analyze syntactic patterns in two types of questions, namely Yes-No questions and WH questions. This study uses the sentence structure theory proposed by Brown and Miller (1991) to understand the elements in sentences and the relationships between their components. Qualitative descriptive methods are applied to observe and analyze interrogative sentence data obtained from native Lio speakers. The results of the analysis show that there are five syntactic patterns used in Yes-No questions and six syntactic patterns in WH questions. These patterns reflect variations in the structure of sentence elements, such as the position of the subject, predicate, and question particles, both for yes-no answers and specific information. This research is expected to contribute to understanding the structure and function of interrogative sentences in the Lio language.